The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2008
DOI: 10.1007/s00268-008-9493-0
|View full text |Cite
|
Sign up to set email alerts
|

Platelets Promote Liver Regeneration under Conditions of Kupffer Cell Depletion after Hepatectomy in Mice

Abstract: After hepatectomy, liver regeneration in the Kupffer cell depleted group was delayed because of lower TNF-alpha expression. Platelets promote liver regeneration even under condition of Kupffer cell depletion by stimulating hepatocyte growth factor and insulin-like growth factor-1 expression, and they activate Akt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
73
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(74 citation statements)
references
References 54 publications
1
73
0
Order By: Relevance
“…The liver-regenerative effect has been shown by several in-vitro experiments and animal models [11,14,[17][18][19]. This has been confirmed by several animal studies [11,14,[20][21][22]. The results of this study confirm that low platelet counts are associated with increased postoperative morbidity and need of operative revision after partial liver resections in humans.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The liver-regenerative effect has been shown by several in-vitro experiments and animal models [11,14,[17][18][19]. This has been confirmed by several animal studies [11,14,[20][21][22]. The results of this study confirm that low platelet counts are associated with increased postoperative morbidity and need of operative revision after partial liver resections in humans.…”
Section: Discussionsupporting
confidence: 77%
“…Platelets contain many growth factors as Platelet Derived Growth Factor (PDGF), Vascular Endothelial Growth Factor (VEGF), HGF, IGF, EGF and TGFb and some cytokines [17,19,30]. Due to those growths factors, platelets play a role in stimulation and acceleration of hepatocyte proliferation resulting in improved liver regeneration [11,18,20,31,32]. Mobilisation and increase of platelet numbers is mediated by thrombopoietin that is mainly produced in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…Murata et al reported that platelets promote liver regeneration in the early period in a murine model [46]. Furthermore, Alkozai et al reported that a low platelet count immediately after partial hepatectomy was associated with delayed recovery of liver function [47].…”
Section: Discussionmentioning
confidence: 99%
“…6 Conversely, following a partial liver resection in animals with a drug-induced thrombocytosis, liver regeneration was accelerated. 9,10 In a clinical study, we showed that a low platelet count is an independent predictor of delayed postoperative liver function recovery following a partial liver resection, suggesting that platelets stimulate liver regeneration also in humans. 11 The molecular mechanisms of platelet-mediated stimulation of liver regeneration are largely unexplored.…”
Section: Introductionmentioning
confidence: 95%